Educating Progressed Learners in Times of COVID-19: How Can Bricolage Help? - Bekithemba Dube; Xolisile P. Ndaba (Research in Social Sciences and Technology- OpenED Network, 2021)
This paper discusses using bricolage to mitigate the struggles faced by progressed learners in rural KwaZulu-Natal, South Africa, in the context of the global COVID-19 pandemic. Most progressed learners perform poorly in many subjects, especially sciences. Their struggle has stimulated the need to find ways to enhance their performance. Reinvented artefacts and processes can be used for emancipation, and to transform agendas for improving the performance of progressed learners. To collect data, we used participatory action research, which uses a thematic approach to make meaning of data. We created a WhatsApp group to enable focus group discussions for collecting data, to circumvent COVID-19 restrictions. The group had 14 members, among whom teachers and learners from rural schools. The study found that the factors that contributed to poor performance were a lack of teaching and learning materials, too few teachers, less than optimal teaching methods and learners’ attitudes towards science subjects. The main argument of the article is that, in this time characterised by the COVID-19 pandemic, embracing bricolage has the impetus to mitigate challenges relating to the education of progressed learners. Thus, it is important to emancipate teachers, so that they can bricolise the environment for teaching and learning.